In the Service of Indoctrination: Humor in Antebellum American Genre Painting - Annus, Irén (AMERICANA E-journal of American Studies in Hungary, 2023)
The construction of national culture and identity, particularly for a newly established nation, is a complex and multifaceted process, one that by definition requires a scrupulous, circumspect, and thoughtful disposition. The historical weight and scale of such an undertaking demand gravity and seriousness that signify a grand enterprise. This was the cultural context within which genre painting found its way to the US in the early nineteenth century. Genre painting (also referred to as morality painting) in Europe often employed humor to provide social criticism, but in the US it was seen as a quintessential style to portray the American nation as unified and democratic through renderings of the daily life of common people – once portrait and history painting had provided the metanarratives and the pantheon of national heroes upon which this new phase of cultural production evolved. The study investigates the key aspects of the ambivalence between genre painting in the old and the new worlds and the ways in which humor was employed in subtle ways in American genre paintings to illuminate the social norms and expectations associated with the up-and-coming middle-class values cemented at the heart of what emerged as the “proper” American nation.